2019
DOI: 10.1111/tpj.14571
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of Arabidopsis NADP‐malic enzyme 1 results in enhanced tolerance to aluminum stress

Abstract: In acidic soils, aluminum (Al) toxicity is a significant limitation to crop production worldwide. Given its Albinding capacity, malate allows internal as well as external detoxification strategies to cope with Al stress, but little is known about the metabolic processes involved in this response. Here, we analyzed the relevance of NADP-dependent malic enzyme (NADP-ME), which catalyzes the oxidative decarboxylation of malate, in Al tolerance. Plants lacking NADP-ME1 (nadp-me1) display reduced inhibition of root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 66 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Cellular malate synthesis and degradation are important for the regulation of the cytosolic pH (Hurth et al., 2005; Smith & Raven, 1979). The absence of NADP‐ME1 encoding ME causes an increase in the amount of malate (Badia et al., 2020). In this research, GO term and KEGG enrichment analysis showed that many genes involved in ME activity were down‐regulated in the A9N3‐treated root compared to the AA‐treated root (Figures S2 and S9; Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular malate synthesis and degradation are important for the regulation of the cytosolic pH (Hurth et al., 2005; Smith & Raven, 1979). The absence of NADP‐ME1 encoding ME causes an increase in the amount of malate (Badia et al., 2020). In this research, GO term and KEGG enrichment analysis showed that many genes involved in ME activity were down‐regulated in the A9N3‐treated root compared to the AA‐treated root (Figures S2 and S9; Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, NADP-ME1 is involved in the regulation of malic acid content in the root apex, and the absence of NADP-ME1 results in an increase in malic acid content. Furthermore, NADP-ME1 also affects the signal transmission process [36]. However, NADP-ME2 plays an important role in the defense mechanism of plants and seems to be involved in the production of reactive oxygen species [37].…”
Section: Iaa Mediated Amf-induced Nadp-mes Expression and Nadp-me Activitymentioning
confidence: 99%
“…The inhibition of the root length was an initial detection of Al toxicity in plants (Matsumoto and Motoda, 2012). Plants with strong Al tolerance usually exhibited high relative root growth (Ma et al, 2018;Badia et al, 2020). In this study, the RRG of OE-ZmAT6 transgenic maize was more than 20% higher than those in the WT.…”
Section: Overexpression Of Zmat6 Improved the Al Tolerance Of Transgementioning
confidence: 56%